Pengaruh Work-life Balance dan Flexible Working Arrangement terhadap Job Performance dengan Dimediasi oleh Employee Engagement - Adinda Siska Witriaryani; Aprilizayanti Putri; David Jonathan; Tengku Mohd Khairal Abdullah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Work-Life Balance and Flexible Working Arrangement on Job Performance with Employee Engagement as a mediating variable. Purposive sampling was applied in this study, where the research area was focused on Jakarta and its surroundings as considered to be the center of the spread of the Covid-19 pandemic in Indonesia, where work from home schemes were mostly applied. Data collection is done online using google form. A total of 208 usable responses were collected from working individuals employed in companies implementing flexible working arrangements. Data were collected and analyzed using SMART PLS ver.3.0. The results showed that flexible working arrangements, although not directly affecting job performance, had several effects when Employee Engagement was introduced as a mediating factor. This finding proposes the full mediating effect of Employee Engagement on Job Performance. In addition, Employee Engagement was also found to mediate the relationship between Work-Life Balance and Job Performance. Therefore, the introduction of Employee Engagement as a mediating variable for Work-Life Balance and Flexible Working Arrangement, will increase the Job Performance variance in this study